FAKTOR PENENTU MOTIVASI TENAGA KESEHATAN MENGIKUTI PENDIDIKAN DAN PELATIHAN BERBASIS THEORY OF PLANNED BEHAVIOUR DI KEMENTERIAN PERTAHANAN - Pongky Sipahutar; Markus Wibowo (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2025)
Education and training in the health sector are very necessary to improve the ability of health workers who can ultimately solve technical medical problems encountered in health services, this study aims to determine whether TPB is able to analyze what factors influence the interest of health workers in participating in health training at the Ministry of Defense Education and Training Agency, using the literature study method, the results of TPB research have illustrated that motivation can be formed including internal and external factors. With the right strategy, such as increasing awareness, providing adequate facilities, improving the quality of training, institutional support, and providing incentives, it is hoped that the participation and enthusiasm of health workers in participating in training can increase significantly. Key Words : theory planned behaviour, motivation, Education, training